Question Number 47850 by maxmathsup by imad last updated on 15/Nov/18 | ||
$${calculate}\:{A}_{{p}} =\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{{x}^{{p}} −\mathrm{1}}{{ln}\left({x}\right)}{dx}\:{with}\:{p}>\mathrm{0}. \\ $$ | ||
Commented bytanmay.chaudhury50@gmail.com last updated on 16/Nov/18 | ||
$${i}\:{have}\:{tried}\:{following}\:{way} \\ $$ $${A}_{{p}} =\int_{\mathrm{0}} ^{\mathrm{1}} \frac{{x}^{{p}} −\mathrm{1}}{{lnx}}{dx} \\ $$ $$\frac{{dA}_{{p}} }{{dp}}=\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\partial}{\partial{p}}\left(\frac{{x}^{{p}} −\mathrm{1}}{{lnx}}\right){dx} \\ $$ $$=\int_{\mathrm{0}} ^{\mathrm{1}} \frac{{x}^{{p}} {lnx}}{{lnx}}{dx} \\ $$ $$=\int_{\mathrm{0}} ^{\mathrm{1}} {x}^{{p}} {dx} \\ $$ $$=\mid\frac{{x}^{{p}+\mathrm{1}} }{{p}+\mathrm{1}}\mid_{\mathrm{0}} ^{\mathrm{1}} =\frac{\mathrm{1}}{{p}+\mathrm{1}} \\ $$ $${dA}_{{p}} =\frac{{dp}}{{p}+\mathrm{1}} \\ $$ $$\int{dA}_{{p}} =\int\frac{{dp}}{{p}+\mathrm{1}} \\ $$ $${A}_{{p}} ={ln}\left({p}+\mathrm{1}\right)+{c} \\ $$ $${now}\:{in}\:{question}\:{p}>\mathrm{0} \\ $$ $${so}\:{here}\:{i}\:{stopped}\:{further}... \\ $$ $${but}\:{if}\:{p}=\mathrm{0}\:{assumed} \\ $$ $${then}\:\int_{\mathrm{0}} ^{\mathrm{1}} \frac{{x}^{{p}} −\mathrm{1}}{{lnx}}{dx} \\ $$ $$\int_{\mathrm{0}} ^{\mathrm{1}} \frac{{x}^{\mathrm{0}} −\mathrm{1}}{{lnx}}{dx}=\mathrm{0}={A}_{{p}=\mathrm{0}} \\ $$ $${then}\: \\ $$ $${A}_{{p}} ={ln}\left({p}+\mathrm{1}\right)+{c} \\ $$ $${A}_{{p}=\mathrm{0}} ={ln}\left(\mathrm{0}+\mathrm{1}\right)+{c} \\ $$ $$\mathrm{0}=\mathrm{0}+{c} \\ $$ $${c}=\mathrm{0} \\ $$ $${A}_{{p}} ={ln}\left({p}+\mathrm{1}\right) \\ $$ $${so}\:{A}_{{p}} =\int_{\mathrm{0}} ^{\mathrm{1}} \frac{{x}^{{p}} −\mathrm{1}}{{lnx}}{dx}={ln}\left({p}+\mathrm{1}\right) \\ $$ $${pls}\:{check}\:{sir}... \\ $$ $$ \\ $$ | ||
Commented bymaxmathsup by imad last updated on 17/Nov/18 | ||
$${changement}\:{ln}\left({x}\right)=−{t}\:{give}\:{A}_{{p}} =−\int_{\mathrm{0}} ^{\infty} \:\:\frac{{e}^{−{pt}} \:−\mathrm{1}}{−{t}}\:\left(−{e}^{−{t}} \right){dt} \\ $$ $$=−\int_{\mathrm{0}} ^{\infty} \:\:\frac{{e}^{−\left({p}+\mathrm{1}\right){t}} \:−{e}^{−{t}} }{{t}}\:{dt}\:=\int_{\mathrm{0}} ^{\infty} \:\frac{{e}^{−{t}} \:−{e}^{−\left({p}+\mathrm{1}\right){t}} }{{t}}{dt}\:{let}\: \\ $$ $${f}\left({p}\right)\:=\int_{\mathrm{0}} ^{\infty} \:\:\frac{{e}^{−{t}} \:−{e}^{−\left({p}+\mathrm{1}\right){t}} }{{t}}\:{dt}\:\Rightarrow{f}^{'} \left({p}\right)\:=\:\int_{\mathrm{0}} ^{\infty} \:\frac{\partial}{\partial{p}}\left(\frac{{e}^{−{t}} \:−{e}^{−{t}} \:{e}^{−{pt}} }{{t}}\right){dt} \\ $$ $$=\int_{\mathrm{0}} ^{\infty} \:\frac{−{e}^{−{t}} \left(−{t}\right){e}^{−{pt}} }{{t}}{dt}\:=\:\int_{\mathrm{0}} ^{\infty} \:{e}^{−\left({p}+\mathrm{1}\right){t}} {dt}\:=\left[−\frac{\mathrm{1}}{{p}+\mathrm{1}}\:{e}^{−\left({p}+\mathrm{1}\right){t}} \right]_{{t}=\mathrm{0}} ^{\infty} \\ $$ $$=\frac{\mathrm{1}}{{p}+\mathrm{1}}\:\Rightarrow{f}\left({p}\right)\:={ln}\left({p}+\mathrm{1}\right)\:+\lambda\:\:\:{but}\:\lambda\:={lim}_{{x}\rightarrow\mathrm{0}} \left({f}\left({p}\right)−{ln}\left({p}+\mathrm{1}\right)\right)=\mathrm{0}\:\Rightarrow \\ $$ $${A}_{{p}} ={f}\left({p}\right)\:={ln}\left({p}+\mathrm{1}\right) \\ $$ $$\bigstar\:\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{{x}^{{p}} −\mathrm{1}}{{ln}\left({x}\right)}{dx}={ln}\left({p}+\mathrm{1}\right)\:\bigstar\:{with}\:{p}>\mathrm{0}. \\ $$ | ||
Answered by tanmay.chaudhury50@gmail.com last updated on 16/Nov/18 | ||
$${we}\:{know} \\ $$ $$\int_{\mathrm{0}} ^{\mathrm{1}} {x}^{{k}} {dx}=\mid\frac{{x}^{{k}+\mathrm{1}} }{{k}+\mathrm{1}}\mid_{\mathrm{0}} ^{\mathrm{1}} =\frac{\mathrm{1}}{{k}+\mathrm{1}} \\ $$ $${now}\:{intregate}\:{both}\:{side}\:{w}.{r}.{t}\:{k}\:{in}\:{the}\:{interval} \\ $$ $${say}\:{q}\:{to}\:{p} \\ $$ $$\int_{{q}} ^{{p}} {dk}\left[\int_{\mathrm{0}} ^{\mathrm{1}} {x}^{{k}} {dx}\right]=\int_{{q}} ^{{p}} \frac{{dk}}{\mathrm{1}+{k}} \\ $$ $${taking}\:{help}\:{from}\:{advanced}\:{level}\:{intregation} \\ $$ $$\int_{\mathrm{0}} ^{\mathrm{1}} {dx}\int_{{q}} ^{{p}} {x}^{{k}} {dk}=\mid{ln}\left(\mathrm{1}+{k}\right)\mid_{{q}} ^{{p}} \\ $$ $$\int_{\mathrm{0}} ^{\mathrm{1}} {dx}\left[\mid\frac{{x}^{{k}} }{{lnx}}\mid_{{q}} ^{{p}} \right]={ln}\left(\frac{\mathrm{1}+{p}}{\mathrm{1}+{q}}\right) \\ $$ $$\int_{\mathrm{0}} ^{\mathrm{1}} \frac{{x}^{{p}} −{x}^{{q}} }{{lnx}}{dx}={ln}\left(\frac{\mathrm{1}+{p}}{\mathrm{1}+{q}}\right)={ln}\left(\mathrm{1}+{p}\right)−{ln}\left(\mathrm{1}+{q}\right) \\ $$ $${now}\:{put}\:{q}=\mathrm{0}\:{both}\:{side} \\ $$ $$\int_{\mathrm{0}} ^{\mathrm{1}} \frac{{x}^{{p}} −\mathrm{1}}{{lnx}}{dx}={ln}\left(\mathrm{1}+{p}\right)\:{ans} \\ $$ | ||